Better Than Welfare? Work and livelihoods for Indigenous Australians after CDEP - Jordan, Kirrily (ANU Press, 2016)
The end of the very long-standing Community Development Employment Projects (CDEP) scheme in 2015 marked a critical juncture in Australian Indigenous policy history. For more than 30 years, CDEP had been among the biggest and most influential programs in the Indigenous affairs portfolio, employing many thousands of Aboriginal and Torres Strait Islander people. More recently, it had also become a focus of intense political contestation that culminated in its ultimate demise. This book examines the consequences of its closure for Indigenous people, communities and organisations. The end of CDEP is first situated in its broader historical and political context: the debates over notions of 'self-determination' versus 'mainstreaming' and the enduring influence of concerns about 'passive welfare' and 'mutual obligation'. In this way, the focus on CDEP highlights more general trends in Indigenous policymaking, and questions whether the dominant government approach is on the right track. Each chapter takes a different disciplinary approach to this question, variously focusing on the consequences of change for community and economic development, individual work habits and employment outcomes, and institutional capacity within the Indigenous sector. Across the case studies examined, the chapters suggest that the end of CDEP has heralded the emergence of a greater reliance on welfare rather than the increased employment outcomes the government had anticipated. Concluding that CDEP was 'better than welfare' in many ways, the book offers encouragement to policymakers to ensure that future reforms generate livelihood options for Aboriginal and Torres Strait Islander Australians that are, in turn, better than CDEP.